PENINGKATAN PRESTASI BELAJAR MATA PELAJARAN EKONOMI DENGAN PENERAPAN STRATEGI PEMBELAJARAN KOLABORASI - Asmaul Husna (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2021)
The aims of this study are: (1) To find out whether the application of the collaborative learning model on the balance material and market structure can improve learning achievement in Economics in Class X IPA 2 students at SMA Negeri 5 Lhokseumawe in the 2017/2018 academic year, (2) To determine the influence of motivation studying Economics after the implementation of the Collaborative Learning Strategy for students of class X IPA 2 at SMA Negeri 5 Lhokseumawe in the 2017/2018 academic year. This research includes classroom action research with a total of 3 cycles and each cycle goes through the stages of planning, implementing, observing, reflecting and evaluating. The research subjects were students of class X-IPA 2 SMA Negeri 5 Lhokseumawe. Data analysis was carried out by: reducing data, presenting data, and drawing conclusions and verification. The data analyzed are teacher activities, student activities, and student learning outcomes. Based on the results of the research that has been presented for three cycles, the results of all the discussions and analyzes that have been carried out can be concluded as follows: (1) The application of collaborative learning has a positive effect, which can increase students' motivation, interest, and learning achievement. (2) The collaborative learning method has a positive impact on improving student achievement by increasing student learning mastery in each cycle, namely cycle I (17 students = 60.71%), cycle II (23 students = 82.14%), cycle III (26 students = 92.26%). (3) Students can work independently or in groups, and are able to take responsibility for all individual and group assignments. (4) Collaborative learning methods can improve the quality of Economics learning.